2013
DOI: 10.4081/rt.2013.e19
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Synchronous Renal Cell Carcinoma of the Bladder Presenting with Gross Hematuria

Abstract: A 57-year old man was referred to the Urology Department due to gross hematuria; abdominal ultrasound revealed an unspecific solid tumor of the left bladder wall. Ultrasound, transurethral resection of the bladder mass with subsequent histological analysis, thoracic and abdominal computed tomography-scan and brain magnetic resonance imaging were performed. He was diagnosed with a bladder metastasis of clear cell renal cell carcinoma (RCC) with concomitant bone, pulmonary, and cerebral metastatic disease of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It is a well-established fact that RCC, like melanoma, is a clinical chameleon as it can metastasize to just about any organ in the body [ 1 10 ]. With common sites of metastasis being the lungs, bones, liver, and brain, RCC still remains quite unpredictable in its pattern of spread [ 1 , 2 , 4 , 5 , 7 , 10 ]. When secondary testicular cancer of renal origin occurs, it usually presents simultaneously or within a year from primary RCC presentation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-established fact that RCC, like melanoma, is a clinical chameleon as it can metastasize to just about any organ in the body [ 1 10 ]. With common sites of metastasis being the lungs, bones, liver, and brain, RCC still remains quite unpredictable in its pattern of spread [ 1 , 2 , 4 , 5 , 7 , 10 ]. When secondary testicular cancer of renal origin occurs, it usually presents simultaneously or within a year from primary RCC presentation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It occurs more commonly in patients with multiple metastases in other organs and confers poor prognosis. 5 Kruck et al, 6 reported a similar case to this one in 2013, where the synchronous diagnosis of bladder metastasis and renal tumor was motivated by a hematuria. In the literature there are few cases reported in the synchronic scenario, as in this case.…”
Section: Discussionmentioning
confidence: 77%
“…Although concurrent bladder and lung cancers are recognized today more frequently than before, with the bladder cancer being mostly the first primary detected, all the reported bladder cancers were transitional cell carcinomas (urothelial carcinoma) [ 18 ]. The possibility of a bladder metastasis from a renal [ 19 ] or ovarian clear cell carcinoma [ 20 ] was excluded in our patient because imaging did not reveal other genitourinary masses. In addition, the RC specimen confirmed the bladder neoplasm location and did not reveal other genital neoplasms.…”
Section: Discussionmentioning
confidence: 99%